2012
DOI: 10.1080/1331677x.2012.11517527
|View full text |Cite
|
Sign up to set email alerts
|

Job Resources, Work Engagement, and Hotel Employee Outcomes: A Time-Lagged Analysis

Abstract: This study develops and tests a research model that investigates work engagement as a mediator of the e¤ ects of coworker and supervisor support on career satisfaction, service recovery performance, job performance, and creative performance. Data were obtained from frontline hotel employees with a time lag of one month and their immediate supervisors in Cameroon. The relationships were tested using LISREL 8.30 through structural equation modeling. The results demonstrated a better …t for the fully mediated mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 26 publications
1
21
0
2
Order By: Relevance
“…Such opportunities help employees develop concrete roadmaps that include the employees’ own strengths and weaknesses in their organizations and labor markets; these roadmaps then assist employees in successfully handling future challenges (Salanova et al, 2010). Ultimately, engaged employees who are not only motivated to achieve their short-term goals, but who also simultaneously cultivate a deep-seated passion toward their work and career, may establish lifelong resources that help them maintain their positive career-related states, such as career satisfaction, career commitment, and low career turnover intention (Barnes & Collier, 2013; Karatepe, 2012; Laschinger, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such opportunities help employees develop concrete roadmaps that include the employees’ own strengths and weaknesses in their organizations and labor markets; these roadmaps then assist employees in successfully handling future challenges (Salanova et al, 2010). Ultimately, engaged employees who are not only motivated to achieve their short-term goals, but who also simultaneously cultivate a deep-seated passion toward their work and career, may establish lifelong resources that help them maintain their positive career-related states, such as career satisfaction, career commitment, and low career turnover intention (Barnes & Collier, 2013; Karatepe, 2012; Laschinger, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…As outcomes of engagement, the following variables have been addressed in recent research: career commitment (Barnes & Collier, 2013); career satisfaction (Karatepe, 2012); and career satisfaction and career turnover intentions (Laschinger, 2012). In particular, satisfaction, commitment, and turnover intentions have all been considered as representative organizational outcomes (Tett & Meyer, 1993).…”
Section: Findings On Work Engagement and Careermentioning
confidence: 99%
See 1 more Smart Citation
“…At the team/unit level, team engagement levels were found to be positively associated with individual engagement, 127 while it was also found that colleagues' engagement levels were associated with individual engagement on days when there was frequent communication. 126 Coworker or colleague support was linked with engagement in two complex studies 229,258 and with group trust in a self-report survey. 73 Torrente et al 226 found that team social resources were linked with individual engagement.…”
Section: Individual Perceptions Of Organisational and Team Factorsmentioning
confidence: 99%
“…In today's highly competitive global environment service firms' success depends on their capacity to consistently deliver satisfying consumption experiences (Karatepe, 2012;Patterson, Cowley, & Prasongsukarn, 2006). Achieving consistent and error-free services should be a goal in service businesses.…”
Section: Introductionmentioning
confidence: 99%